Governing through Goals : Sustainable Development Goals as Governance Innovation - Biermann, Frank, 1967-; Kanie, Norichika, 1969- (Book collections on Project MUSE., 2017)
A detailed examination of the UN's Sustainable Development Goals and the shift in governance strategy they represent.